Analysis of the Influence of Endorser and Brand Credibility on Samsung Brand Equity - Sani Isah; Eva Andriani; Syah Amin Albadry; Iswahyu Pranawukir; Darmawanto (International Journal of Economics (IJEC), 2024)
This research was conducted with the aim of obtaining explanations and information regarding the influence of brand credibility on the equity of the brand itself. Apart from that, there is the influence of endorser credibility which has a correlation with brand equity. The influence of brand credibility on brand equity and also the influence of brand credibility on the brand equity of Samsung users in Jakarta. This research was conducted in the Jakarta area, presenting around 170 respondents. The method used in this research is a deep purposive sampling method presentation of data and the process of collecting it. Apart from that, path analysis techniques were also carried out in this research. The results of this research show that the credibility of the endorser has a positive influence and also plays a significant role in the credibility of the brand. Brand credibility has quite an important role as a partial mediation by providing influence between endorser credibility and also the equity of the Samsung brand. Samsung must increase the credibility of positive endorsers in order to create strong brand equity.